An improved power quality modified DC‐DC converter fed PMBLDC motor drive system for household applications. (29th September 2020) - Rathore, Kuldeep Singh; Kalla, Ujjwal Kumar; Palwalia, Dheeraj Kumar; Singh, Bhim
Summary: In recent time, the permanent magnet brushless direct current motor (PMBLDCM) is advantageous in comparison to the other motor‐drives having same rating including but not limited to, better torque to inertia ratio, reliable, robustness, efficiency, low electromagnetic interference problems, and extraordinary performance over a wide speed control. To meet the requirements of international standards of power quality like IEC 61000‐3‐2 and IEEE 519, the PMBLDCM‐drive has to utilize the power quality improved DC‐DC converters. The conventional drive system consisting of a diode bridge rectifier (DBR) fed PMBLDCM does have a very high value of DC link capacitor. This type of circuit arrangement has poor power factor at source side. This paper presents an improved power quality modified DC‐DC converter fed PMBLDCM‐drive system for household applications. This system includes a power factor corrected (PFC) modified DC‐DC converter operating in continuous current mode (CCM). This system configuration is highly suitable for PMBLDCM‐drive based household applications because the ripple in the output DC link current is very less, which significantly reduces the torque ripples of the PMBLDCM‐drive system. The high frequency switching losses of voltage source inverter (VSI) are reduced by using the Hall‐Effect sensor based electronic commutation at fundamental frequency. This reduction in losses significantly improves the overall efficiency of the PMBLDCM‐drive system. Simulated and hardware results are included to verify the performance at dynamic state and steady‐state of the PMBLDCM‐drive system. Obtained results show that this system is following the international standards like IEC61000‐3‐2 and IEEE 519 of power quality improvement. Abstract : This article presents an improved power quality modified DC‐DC converter fed permanent magnet brushless direct current (PMBLDC) motor drive system for household applications. This system configuration is highly suitable for PMBLDC motor drive‐based household applications because the ripple in the output DC link current is very less, which significantly reduces the torque ripples of the PMBLDC motor.